2014
DOI: 10.1111/jdi.12190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal impairment on cognitive function during a 3‐year follow up in elderly patients with type 2 diabetes: Association with microinflammation

Abstract: Aims/IntroductionWe investigated the effect of renal impairment on cognitive function during a 3‐year follow up in elderly type 2 diabetic patients, and an association with microinflammation.Materials and MethodsFour cognitive function tests – Mini‐Mental State Examination (MMSE), word recall, Digit Symbol Substitution (DSS) and Stroop Color Word – were carried out in 67 patients. Renal impairment was defined as the presence of albuminuria and a decline in estimated glomerular filtration (eGFR) <60 mL/min/1.73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In addition, parallel changes in severity and improvement of chronic kidney disease and some cognitive functions have been reported in the recent subanalysis of the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial 5 . In this regard, we reported that changes in albuminuria, but not eGFR, were strongly correlated with changes in word recall during a 3-year follow up in elderly diabetic patients 6 . However, in that study, a cross-sectional evaluation of an association between cognitive functions and albuminuria or eGFR produced different results from those of a longitudinal evaluation.…”
mentioning
confidence: 82%
“…In addition, parallel changes in severity and improvement of chronic kidney disease and some cognitive functions have been reported in the recent subanalysis of the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial 5 . In this regard, we reported that changes in albuminuria, but not eGFR, were strongly correlated with changes in word recall during a 3-year follow up in elderly diabetic patients 6 . However, in that study, a cross-sectional evaluation of an association between cognitive functions and albuminuria or eGFR produced different results from those of a longitudinal evaluation.…”
mentioning
confidence: 82%
“…After adjusting for potential confounders, moderate renal insufficiency was associated with a 37% increased risk of dementia over a median 6 yr follow‐up in individuals without prevalent dementia (n = 3349) . A study of elderly type 2 diabetic patients with a 3‐year follow up showed that renal impairment was also related to cognitive decline . The reduction in the one‐year MMSE was higher in hemodialysis (HD) patients than elderly patients .…”
Section: Evidence Of Ckd‐related Physical Frailty and Cognitive Impaimentioning
confidence: 99%
“…Another survey indicated that the high prevalence of WMH in HD, older age, female patients with high blood pressure was strongly associated with the presence of both PVH and DSWMH . Increased baseline levels of hs‐CRP, TNF‐α and IL‐6 were associated with renal impairment, cerebral SVD and cognitive function . Fibrinogen, an acute‐phase protein and inflammation marker, was elevated in CKD patients, which predicts cognitive performance in CKD and as a marker of late‐life CI .…”
Section: Risk Factors Of Ckd and Biological Mechanisms Of Ckd‐inducedmentioning
confidence: 99%
See 2 more Smart Citations